2013
DOI: 10.3390/md11030788
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Anti-Inflammatory Eunicellin-Based Diterpenoids from the Soft Coral Cladiella krempfi

Abstract: Five new eunicellin-based diterpenoids, krempfielins E–I (1–5) and seven known compounds (6–12) were isolated from the organic extract of a Taiwanese soft coral Cladiella krempfi. The structures of the new metabolites were elucidated on the basis of extensive spectroscopic analysis. Metabolites 5, 6, 10 and 12 were shown to exhibit cytotoxicity against a limited panel of cancer cell lines. Furthermore, compounds 6 and 10 could potently inhibit the accumulation of the pro-inflammatory iNOS protein, and 6 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…NMR spectroscopic data of 1 (Table 1) showed the presence of one acetoxy group (δ C 169.6 and 22.4; δ H 2.12, s, 3H) and one methoxyl group (δ C 57.0 and δ H 3.34, 3H, s). The NMR data of 1 was found to be similar to the known compound, 7 [22,25] (Chart 1). Comparison of the NMR data of them revealed that the only difference between both compounds arises from the replacement of the n -butyryloxy group at C-3 in 7 by one acetoxy group in 1 .…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…NMR spectroscopic data of 1 (Table 1) showed the presence of one acetoxy group (δ C 169.6 and 22.4; δ H 2.12, s, 3H) and one methoxyl group (δ C 57.0 and δ H 3.34, 3H, s). The NMR data of 1 was found to be similar to the known compound, 7 [22,25] (Chart 1). Comparison of the NMR data of them revealed that the only difference between both compounds arises from the replacement of the n -butyryloxy group at C-3 in 7 by one acetoxy group in 1 .…”
Section: Resultsmentioning
confidence: 55%
“…The soft coral Cladiella krempfi has been found to generate several types of metabolites including eunicellin-type diterpenoids [16,17] and pregnane-type steroids [18,19,20]. Our previous study on the bioactive secondary metabolites of a Taiwanese soft coral Cladiella krempfi also resulted in the isolation of a series of new eunicellin-based diterpenoids, krempfielins A–I [21,22]. In this paper, we further report the discovery of four new eunicellin-based diterpenoids, krempfielins J–M ( 1 – 4 ), along with two known diterpenoids sclerophytin F ( 5 ) [23] and litophynol B ( 6 ) [24] (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…The relative configuration of 1 was thus established. Comparison of the 1 H and 13 C NMR spectroscopic data of 1 with those of its 7,16-dehydration derivative, krempfielin E ( 4 ) [ 16 ], further confirmed the structure of 1 .…”
Section: Resultsmentioning
confidence: 82%
“…Soft corals of the genus Cladiella have been known to be rich sources of eunicellin-type metabolites and several bioactivities of these compounds have been studied [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Our previous studies on the soft coral Cladiella krempfi have resulted in the isolation of a series of new eunicellin-based diterpenoids, krempfielins A–P [ 15 , 16 , 17 , 18 ]. Our contineous investigation on the chemical constituents of soft coral C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation